2014
DOI: 10.1111/idj.12102
|View full text |Cite
|
Sign up to set email alerts
|

In situ clinical evaluation of a stabilised, stannous fluoride dentifrice

Abstract: Objectives: To compare the erosion protection efficacy of a stabilised, stannous fluoride (SnF 2 ) dentifrice versus a sodium fluoride (NaF) dentifrice using a modified in situ clinical model. Methods: This study, a randomised parallel group in situ design with in vivo product use and ex vivo acid challenge, compared: A, a dentifrice containing 1,450 ppm F as NaF; B, a dentifrice containing 1,450 ppm F (1,100 ppm F as SnF 2 + 350 ppm F as NaF); and T, tap water. Sample size was n = 4 per group (total of 12 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 19 publications
0
33
0
1
Order By: Relevance
“…The randomized in situ study comparing the anti-erosive efficacy of Sn-containing sodium fluoride toothpaste with a sodium fluoride and potassium nitrate toothpaste showed the lower enamel loss after use of the stabilised Sn-containing sodium fluoride toothpaste, which was measured by contact profilometry [28]. Also Bellamy et al [29] in contact profilometry readings using modified model in situ confirmed the greater erosion protection benefit of toothpaste with stabilised SnF 2 compared to sodium fluoride toothpaste.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The randomized in situ study comparing the anti-erosive efficacy of Sn-containing sodium fluoride toothpaste with a sodium fluoride and potassium nitrate toothpaste showed the lower enamel loss after use of the stabilised Sn-containing sodium fluoride toothpaste, which was measured by contact profilometry [28]. Also Bellamy et al [29] in contact profilometry readings using modified model in situ confirmed the greater erosion protection benefit of toothpaste with stabilised SnF 2 compared to sodium fluoride toothpaste.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, Baig et al [24] comparing the ability of NaF and SnF 2 to the inhibition of powdered hydroxyapatite dissolution in buffered acidic solution, found the greater acid resistant of hydroxyapatite after the use of SnF 2 than NaF solutions and similar results after the immersion into slurries of marketed toothpastes containing those chemical compounds. In several studies simulating the oral condition, the efficacy of tin ions against erosion was assessed on enamel specimens coated by salivary pellicle [12,[25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Hystad Hove et al [2014] also showed that a tin-containing dentifrice reduced enamel wear in comparison to the negative control group (no fluoridation). Similarly, Bellamy et al [2014] observed that treatment with the tin-containing dentifrice resulted in more than 85% less surface loss than the negative control (no fluoridation). And when comparing the effect of exposure to dentifrice slurry (erosion-only) or slurry together with toothbrushing (erosion-abrasion), Schlueter et al [2013] showed that the tin-containing dentifrice had a significantly better efficacy in both experimental models, resulting in a reduction in enamel loss of more than 50%.…”
Section: Polyvalent Metal Ions Products Containing Tin Ionsmentioning
confidence: 82%
“…Assim sendo, estudos in situ, são utilizados para contornar as dificuldades de realização de estudos de erosão dentária in vivo 53 , oferecendo ainda a vantagem da padronização dos desafios erosivos, como concentração, volume e duração da exposição ao agente erosivo iguais para todos os grupos de estudo, minimizando a variabilidade 54 , somada a exposição dos espécimes ao ambiente bucal. Na maior parte dos estudos in situ já realizados (quadro 01) a aplicação da pasta de CPP-ACP foi feita depois do desafio erosivo.…”
Section: Discussionunclassified